IMPLEMENTASI PROGRAM GANDENG GENDONG PADA SUB PROGRAM “NGLARISI” DALAM MENINGKATKAN EKONOMI PELAKU UMKM DI KEMANTREN PAKUALAMAN KOTA YOGYAKARTA - Putri, Titania Permata; Putranto, Arif Kuncoro Dwi (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
Gandeng Gendong Program, implemented by the Yogyakarta City Government, aims to reduce poverty levels and improve the welfare of Micro, Small, and Medium Enterprises (MSMEs). This program is integrated into the Jogja Smart Service (JSS) application under the "Nglarisi" menu, which allows local government agencies (Organisasi Perangkat Daerah or OPD) to order meeting refreshments from MSMEs participating in the Gandeng Gendong Program. This research uses a qualitative approach and a descriptive method. This research uses interview, observation and documentation method. Determination of informants in this research was carried out using purposive sampling. The theoretical framework used in this study is based on Grindlee's theory as outlined in Subarsono (2011:10-16), which includes: (1) Content of Policy; and (2) Context of Implementation. The objective of this research is to understand the implementation of the Gandeng Gendong Program within the "Nglarisi" sub-program in enhancing the economy of MSME operators in the Pakualaman District of Yogyakarta City.The implementation of the Gandeng Gendong Program within the "Nglarisi" sub-program has been carried out effectively but has not yet reached its full potential.